Changes in Mobility of the Golden Hamster with Induction of an IL-1-Induced Arthritis - I. G. Otterness; M. L. Bliven; A. J. Milici (Hindawi Limited, 1994)
Many studies in animals have examined biochemical, immune and histological changes during arthritis; however, the study of the effects of arthritis on mobility has been largely neglected. Interleukin-1, administered by the intraarticular route into hamster knee joints, resulted in inhibition of spontaneous wheel running activity; however, the effect was transient, lasting only through the evening following IL-1 administration. A further injection of IL-1 2 days later showed still greater inhibition of running. The effect again did not extend beyond the first evening after injection. IL-1α and IL-1β showed equivalent effects on mobility, and no evidence was seen for cooperative interaction between them. A 50% inhibition of running occurred at a dose of approximately 10 ng/knee of IL-1α. The effect appeared not to be systemic since intraperitoneal injection required microgram amounts of IL-1 for an equivalent inhibition. At the time mobility had been restored to normal, histological examination showed the continued presence of inflammatory cells, soft tissue swelling and cartilage proteoglycan loss. These results suggest a lack of correlation between inhibition of mobility and histopathological changes in cartilage and soft tissue.